PERFORMANCE OF NUBIAN GOATS FED NATRON SALT SUPPLEMENTATION: FED AND WATER INTAKE, BODY WEIGHT AND FEED CONVERSION RATIO (Journal of Veterinary Medicine and Animal Production, 2022)
This study was conducted to investigate the performance of Nubian goat fed a concentrate diet supplemented with natron levels at 0- 5%. where a total of 25 Nubian goat’s kids of both sexes (7 - 9 month old) were used. They were divided into five equal groups each randomly allocated to the concentrate diet containing one of the above natron levels. The experimental period covered the three seasons; dry and wet summer, and winter. The measurements included water and food intakes, body weight changes and feed conversion ratio.The responses showed a significant increase (P
Keywords: Natron salt supplementation; Nubian goats; seasons; feed intak; feed conversionrate